Valorization of wipe wastes for the synthesis of microporous carbons and their application in CO2 capture, gas separation and H2-storage - Garcia, Enrique Vilarrasa (2023)
Wipe wastes have been used as a cellulosic source to synthesize biochars. Prior to the synthesis of the adsorbents by the pyrolysis of wipes wastes, this waste was treated to remove the pathogenic agents. Then, the wipe wastes were pyrolyzed between 500 and 900 ◦C to obtain biochars, whose microporosity increased proportionally to the pyrolysis temperature, achieving a maximum CO2-adsorption uptake of 2.53 mmol/g at a pressure of 760 mm of Hg and 25 ◦C for the biochar pyrolized at 900 ◦C. The synthesized biochars are also highly selective towards CO2-adsorption in CO2/N2 or CO2/H2 mixtures. Hence, these adsorbents have shown a great potential to be used in flue gas treatment and H2-purification processes. Biochar treatment with KOH further improves microporosity due to chemical activation although the addition of a large amount of KOH leads to excessive microporosity causing a collapse in the pore structure and decreasing CO2-adsorption capacity.